Clinico pathological study of cervical lymphadenopathy - Melkundi, Renuka S.; Melkundi, Sateesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: This study was carried out with a broad objective of assessing relative diagnostic efficacy of the clinical evaluation, fine needle aspiration biopsy and open biopsy. The objective was to study the confirmatory diagnosis of the underlying pathological variants, the incidence of the malignancies, presenting with cervical lymphadenitis and also to diagnose various etiologies of cervical lymphadenitis in all age groups. Methods: Patients attending the ENT and surgery OPD of BTGH and General hospital, Gulbarga, of all age groups and both genders having the neck swelling for more than three weeks were subjected for the study. Results: This study has shown that the incidence of tubercular lymphadenitis is more in the age group of 1st and 2nd decade and in low socioeconomic status while secondaries are more common in the elderly age group. Conclusions: From this study it can be concluded that in cervical lymphadenopathy clinical evaluation followed by FNAC is most reliable diagnostic tool, which is easy to perform, cost effective, speedy results can be obtained and accurate. The main requirement for this is the specialist input.